Ethnic Economic Inequality and Fatalities From Terrorism. Issue 11 (June 2022) - Fleming, Christopher M.; Manning, Matthew; Pham, Hien-Thuc; Vorsina, Margarita
Few studies have explored the influence of horizontal (i.e., among group) inequalities on terrorism, yet it seems plausible that these inequalities may be relevant. Employing data from the Global Terrorism Database and Ethnologue, this article examines the effect of ethnic economic inequality on domestic terrorism for 130 countries over the period 2001 to 2018. We present evidence that higher degrees of ethnic inequality lead to higher numbers of terrorist attacks as well as a higher number of people killed or injured. This positive association between ethnic inequality and terrorism is robust to alternative measures of ethnic inequality, omission of influential countries and regions, the inclusion and exclusion of controls, and alternative estimation strategies. In contrast, countries with high degree of political freedom and high governance quality tend to suffer less from terrorism. Promoting economic equality among ethnic groups, therefore, has the potential to reduce the risk of domestic terrorism. We propose that a critical step towards promoting this equality is to enhance social inclusion. The benefits of increasing social inclusion extend beyond simply reducing the incidence of terrorism and inter-racial violence; creating a socially inclusive society is a social justice imperative and the responsibility of policymakers, social institutions, civil society, and the private sector. It is also consistent with the notion of inclusive economic growth, as championed by organizations such as the OECD and the United Nations Development Program.